1999
DOI: 10.1046/j.1432-1327.1999.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation and origin of the mitochondrial membrane potential in human cells lacking mitochondrial DNA

Abstract: Mammalian mitochondrial DNA (mtDNA) encodes 13 polypeptide components of oxidative phosphorylation complexes. Consequently, cells that lack mtDNA (termed r8 cells) cannot maintain a membrane potential by proton pumping. However, most mitochondrial proteins are encoded by nuclear DNA and are still imported into mitochondria in r8 cells by a mechanism that requires a membrane potential. This membrane potential is thought to arise from the electrogenic exchange of ATP 4± for ADP 3± by the adenine nucleotide carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
134
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 47 publications
(63 reference statements)
15
134
0
Order By: Relevance
“…The mitochondrial pellet was washed in STE, and the supernatant was acetone-precipitated. Assays of the mitochondrial enzyme citrate synthase and of the cytosolic enzyme lactate dehydrogenase confirmed that this fractionation procedure was effective, with less than 5% lactate dehydrogenase activity in the mitochondrial fraction that contained about 40% of the total citrate synthase activity (36).…”
mentioning
confidence: 80%
“…The mitochondrial pellet was washed in STE, and the supernatant was acetone-precipitated. Assays of the mitochondrial enzyme citrate synthase and of the cytosolic enzyme lactate dehydrogenase confirmed that this fractionation procedure was effective, with less than 5% lactate dehydrogenase activity in the mitochondrial fraction that contained about 40% of the total citrate synthase activity (36).…”
mentioning
confidence: 80%
“…Mitochondrial dysfunction resulting from PNPase deficiency led to secondary effects including reduced ATP production. In addition to reduced ATP production from defective OX-PHOS, a complementary mechanism for further reducing ATP might include increased ATP catabolism as an adaptive response, through the ATP synthase acting as an ATP hydrolase, which would help stabilize ⌬ and inhibit the onset of apoptosis (2). Reduced cell energy charge, in turn, would enhance the phosphorylation of AMPK, which could slow cell growth through a potential link to p53-mediated inhibition of the cyclin E cell cycle checkpoint protein (21,31).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomycin-sensitive complex V ATP hydrolysis activity was determined by incubating 30 g mitochondria in 1 ml 100 mM Tris buffer, pH 8.0, containing 50 mM KCl, 2 mM MgCl 2 , 0.2 mM EDTA, 200 M NADH, 1 mM phosphoenolpyruvate, 2 U/ml lactate dehydrogenase, 4 U/ml pyruvate kinase, 2.5 mM Mg-ATP, 4 g/ml rotenone, 300 nM antimycin A, and 2 mM KCN in the presence or absence of 5 g/ml oligomycin. The oxidation of NADH was followed at 340 minus 400 nm for 7 min at 30°C (2). Enzyme activities are shown as nmol/min/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ by ANT (Buchet and Godinot, 1998;Appleby et al, 1999;Chandel and Schumacker, 1999;Arnould et al, 2003). Oligomycin (which binds and inhibits only the F 0 portion of F 0 F 1 -ATPase) does not eliminate ATPase activity and ⌬⌿m in rho zero cells, because they are devoid of F 0 (Buchet andGodinot, 1998 Appleby et al, 1999).…”
Section: Discussionmentioning
confidence: 99%